PEMANFAATAN INDERAJA DAN SISTEM INFORMASI GEOGRAFIS (SIG) DALAM INVENTARISASI LAHAN KRITIS DI KABUPATEN KOLAKA UTARA - . Baharuddin (Forestry Faculty of Universitas Hasanuddin, 2010)
At this time the technology required to conduct a study of land mainly related to land change and land condition analysis. To anticiapate this need for technology Remote Sensing and Geographic Information System (GIS) that can quickly and accurately to conduct a study on land resources. Critical land is a condition of land which is the result of an error in the maintenance and land management. Kolaka Utara Regency a new district which has the problem of land mainly biophysical and social condition.In this case the methode used is to land suitability analysis approach based on FAO and determination based on the rules Director General Land Rehabilitation and Social Forestry – DEPHUT, SK.167/V-SET/2004, combined with productivity data field based on their utilization. Based on the analysis with Remote Sensing and GIS in Kolaka Utara Regency result that is dominated by protected forest area of 163.376,51 ha (53,0 %), followed by limited production forest 65.887,63 ha (21 %), cultivation area 60.977,75 ha. (19,6 %) and production forest convertion 20.258,94 ha (6.5 %). Land use and land cover largest is forest area of 177.850,02 ha (57,3 %), cocoa palantation area 91.066.80 ha (29,3 %), garden mixed area18.517,76 ha (6,0 %), shrub area 11.615,40 ha (3,7 %), and clove plantation area 4.067,93 ha ( 1,3 %). Potential land critical area is 39.040,96 ha (12,6 %), land rather critical is 13.513,43 ha (4,4 %), critical land is 47.534,21 ha, (15,3 %) and land critical immensely is 19.509,42 ha (6,3 %), and land while the rest is not critical is 190.902,81 ha (61,5 %). Degraded land spread in all areas well outside the region (cultivate area) and within region (forest area). Key words: Inderaja, SIG, critical land